2010
DOI: 10.1111/j.1346-8138.2010.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing ofTrichophyton mentagrophytesvar.interdigitaleisolated in a university hospital in Japan based on the non‐transcribed spacer region of the ribosomal RNA gene

Abstract: Detecting intraspecies polymorphisms in fungi causing dermatophytoses is important in elucidating routes of infection and determining whether Tinea recurrence is caused by exacerbation or re-infection. In fungi, the non-transcribed spacer region (NTS) of the ribosomal RNA gene shows the greatest accumulation of base sequence mutations. We therefore assessed NTS sequences in 64 clinical isolates of Trichophyton mentagrophytes var. interdigitale, the second most common species of dermatophytes in Japan. These is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
2
19
1
Order By: Relevance
“…However, analysis of the non-transcribed spacer (NTS) region of the rRNA genes has been reported to be a more robust technique for strain typing of some dermatophyte species, such as Trichophyton rubrum (8), Trichophyton tonsurans (9-12), and T. mentagrophytes var. interdigitale (13)(14)(15). Our previous study indicated that Southern blot hybridization of the NTS region is useful for the discrimination of A. benhamiae strains (16), and simple molecular methods are required to be developed for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…However, analysis of the non-transcribed spacer (NTS) region of the rRNA genes has been reported to be a more robust technique for strain typing of some dermatophyte species, such as Trichophyton rubrum (8), Trichophyton tonsurans (9-12), and T. mentagrophytes var. interdigitale (13)(14)(15). Our previous study indicated that Southern blot hybridization of the NTS region is useful for the discrimination of A. benhamiae strains (16), and simple molecular methods are required to be developed for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…All of the clinical isolates of T. mentagrophytes var. interdigitale assayed showed homogeneous mitochondrial DNA genotype, the same as that of A. vanbreuseghemii and different from those of two other teleomorphs of T. mentagrophytes, A. benhamiae and A. simii 8) . On the other hand, the genotypes of ITS were also homogeneous among 64 T. mentagrophytes var.…”
Section: Discussionmentioning
confidence: 75%
“…interdigitale 4,8) . lesions related in animals are granular to powdery cultures and identified as T. mentagrophytes var.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations